Inflation and consumption in equality in 2012–2017 - T. I. Gordiyevich; P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность")
In the article the analysis of inequality in consumption in 2012–2017, in particular, the final consumption expenditure of households structure of consumer expenditure of households, consumer price indices for goods and services — 10 % groups. During the analysis, the following regularities are clarified. In the context of financial destabilization, the degree of inequality decreases, and in the conditions of stabilization and reduction of inflation — it grows. Inequality is affected by an asymmetric pattern of consumption: a high proportion of food consumption in low — cost groups and a low proportion in high-cost groups. Also detected asymmetry in the consumption of transport: high share of consumption of transport in the groups with high and low costs — low costs. Due to the peculiarities of the structure, asymmetric inflation is manifested. In groups with increasing costs, the consumer price index is declining. In general, the analysis shows that inequality in consumption and inflation in socioeconomic groups depend primarily on the structure of consumption